COVID-19 and Limitations to the International Right to Freedom of Religion or Belief - Plessis, Du (A journal of church and state, 2021)
The largest pandemic outbreak in the twenty-first century to date is the coronavirus disease (COVID-19), causing, as of October 6, 2020, 1,051,475 deaths worldw